ShareAlike Your Data: Self-referential Usage Policies for the Semantic Web. - Krötzsch, M; Speiser, S (Springer, 2011)
Numerous forms of policies, licensing terms, and related conditions are associated with Web data and services. A natural goal for facilitating the re-use and re-combination of such content is to model usage policies as part of the data so as to enable their exchange and automated processing. This paper thus proposes a concrete policy modelling language. A particular difficulty are self-referential policies such as Creative Commons ShareAlike, that mandate that derived content is published under some license with the same permissions and requirements. We present a general semantic framework for evaluating such recursive statements, show that it has desirable formal properties, and explain how it can be evaluated using existing tools. We then show that our approach is compatible with both OWL DL and Datalog, and illustrate how one can concretely model self-referential policies in these languages to obtain desired conclusions. © 2011 Springer-Verlag.